Antioxidant Activity and Hepatoprotective Potential of Polyalthia longifolia and Cassia spectabilis Leaves against Paracetamol-Induced Liver Injury - L. Jothy, Subramanion; Aziz, Azlan; Yeng, Chen; Sasidharan, Sreenivasan (Hindawi Publishing Corporation, 2012)
In the present study, in vitro antioxidant, free radical scavenging capacity, and hepatoprotective activity of methanol extracts from Polyalthia longifolia and Cassia spectabilis were evaluated using established in vitro models such as ferric-reducing antioxidant power (FRAP), 2,2-diphenyl-1-picryl-hydrazyl (DPPH•), hydroxyl radical (OH•), nitric oxide radical (NO•) scavenging, metal chelating, and antilipidperoxidation activities. Interestingly, all the extracts showed considerable in vitro antioxidant and free radical scavenging activities in a dose-dependent manner when compared to the standard antioxidant which verified the presence of strong antioxidant compound in leaf extracts tested. Phenolic and flavonoid content of these extracts is significantly correlated with antioxidant capacity. Since P. longifolia extract was exhibited better in vitro antioxidant activities, it was subjected for in vivo hepatoprotective activity in paracetamol-intoxicated mice. Therapy of P. longifolia showed the liver protective effect on biochemical and histopathological alterations. Moreover, histological studies also supported the biochemical finding, that is, the maximum improvement in the histoarchitecture of the liver. Results revealed that P. longifolia leaf extract could protect the liver against paracetamol-induced oxidative damage by possibly increasing the antioxidant protection mechanism inmice. Our findings indicated that P. longifolia and C. spectabilis have potential as good sources of natural antioxidant/antiaging compounds.